Razak Abdul Aziz’s Pepatah Episodes: Re-Imaging the Malay Proverbs through Piano Music - Zamani, Mohd Fairuz (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
Proverb sits under the umbrella of figurative language and is used to sweeten speeches. In Malay, pepatah is the equivalent of this form of figurative language. Razak Abdul Aziz, a Malaysian composer, selected a set of Malay proverbs and adapted them into his piano work, Pepatah Episodes. The composer follows the tradition of piano programme music that uses figurative language elements championed by composers such as Alexander Scriabin, Claude Debussy, and Maurice Ravel. This paper aims to investigate the pepatahs chosen to be paired with the written music, expounding the programme in the movements for piano. Using the programme music analysis framework by Burkholder et al. (2014) and Kregor (2015), the finding shows that the composer chose the pepatahs for one of the three (3) portrayals: (i) imageries in the pepatah (ii) imageries in the meaning, and (iii) imageries in pepatah and meaning. The programme analysis shows that from the nine (9) movements written for piano, four (4) movements portray imageries in the pepatah, three (3) movements portray imageries in the meaning, and two (2) movements portray imageries in the pepatah and meaning. Razak Abdul Aziz challenges the conventions of programme music by having the pepatah set after the music is written, demanding the performer to read it aloud before performing and having the portrayal of the pepatah in the mentioned ways. This provides a different perspective for other composers to produce works using similar frameworks and scholars to analyse musical works.